2022
DOI: 10.1111/ijfs.15827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germination time on phenolics, antioxidant capacity, in vitro phenolic bioaccessibility and starch digestibility in sorghum

Abstract: Summary The effects of germination time on phenolic, flavonoid, anthocyanin, antioxidant capacities, inhibition capacity of α‐amylase, bioaccessibility of phenolic and digestibility of starch in sorghum were evaluated in this study. The levels of total phenolic, flavonoid and anthocyanin in germinated sorghum for 48 h increased by 39.74%, 37.28% and 52.21%, respectively. Germination also increased the composition of phenolic, flavonoid and anthocyanin in sorghum, and their antioxidant capacity and inhibitory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…However, the red- and white-pigmented pericarp varieties did not exhibit a significant difference in TPC. The results are comparable with the findings of [ 43 ], who reported a 39.74% increase in the TPC after 48 h of germination in sorghum. Many studies showed that germination processes clearly increase TPC in quinoa, amaranth, buckwheat, and millet [ 21 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the red- and white-pigmented pericarp varieties did not exhibit a significant difference in TPC. The results are comparable with the findings of [ 43 ], who reported a 39.74% increase in the TPC after 48 h of germination in sorghum. Many studies showed that germination processes clearly increase TPC in quinoa, amaranth, buckwheat, and millet [ 21 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 91%
“…The germination process was significantly effective in both red and white grains and reached its highest level (184.94 mg AAE/100g and 55.46 mg AAE/100g, respectively) after 7 days of germination. Previous studies have also indicated that germination has an enhancing impact on the DPPH scavenging activity of sorghum grains [ 43 , 47 ]. The DPPH scavenging activity of germinated wheat, barley, and millet grain was increased significantly from 1.37–1.64 g AAE/g to 3.19–3.76 g AAE/g after 72 h of germination [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…44 The initial values of the total phenolic content of the three varieties for germination had slight differences, with the initial values ranging from about 64.29 mg kg −1 -75.85 mg kg −1 , and increased to 236.30 mg kg −1 -297.78 mg kg −1 during the 5 days germination; the total phenolic content of KZ showed the largest increase (221.93 mg GAE kg −1 ). These results agreed with those of Li et al 14 and Rasera et al, 15 which indicated that the moderate germination pretreatment was benecial to the increase in total phenolic content. The increase in total phenolic content may be attributed to the fact that germination pretreatment promoted the conversion of binding phenols to free phenols, which were more readily released in oils.…”
Section: Total Phenolic Content and Antioxidant Capacity Of Axseed Oilsupporting
confidence: 92%
“…Nutrients, such as vitamins, minerals, and limiting amino acids, increase during germination. 13 Furthermore, a large range of plant seeds, such as sorghum, 14 mustard grains, 15 quinoa, 16 and flaxseed, 17 which release bound phenolic compounds because of the degradation of the plant cell wall after germination, had a high content of total phenolic. Furthermore, germination-treated seeds had outstanding oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high nutritional values of barley grain and the presence of bioactive substances with antioxidant properties, especially phenolic compounds such as phenolic acids, flavonols or anthocyanins, the consumption importance of barley has increased in recent years due to its health‐beneficial properties (2020; Nowak et al ., 2023). Seed germination, which is said to be the first stage of the plant development cycle, has been explained as a complex physiological process that occurs as a result of the absorption of water by the seeds and the emergence of the root, which is the component part of the future plant, as the final point (Özcan & Juhaimi, 2014; Han & Yang, 2015; Paucar‐Menacho et al ., 2018; Alkaltham et al ., 2020; Li et al ., 2022). Various studies have been carried out showing that the bioavailability of minerals and the amount of phenolic constituents in seeds increase with germination (Pjak et al ., 2019; Chu et al ., 2020; Oghbaei & Prakash, 2020; Pilco‐Quesada et al ., 2020; Ge et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%